Amazon to become the undisputed retail champion? - Correia, Francisco Maria Marques Batista de Morais (2021)
The purpose of this dissertation is to analyze the potential acquisition of Target Corporation by Amazon. The retail industry has been consistently growing in past years, without any signs of slowing down. Even though the Covid-19 pandemic fueled the global shift from physical to online retailing, this acquisition is presented as viable option for a company like Amazon. In order to leverage on its remarkable year results and accentuate its position as the worldwide market leader in the retailing industry, it is proposed a possible strong entrance in the brick-and-mortar retail, in the US, hinted by the 2017 acquisition of Whole Foods. The proposed acquisition is a direct response to Walmart, Amazon’s main competitor in the US, which has recently gained market share in the online retail industry. The recommended bid price is $202.60 per share, which accounts for a 27% acquisition premium over the market price at the 11th of December 2020. This valued is justified by net synergies of $37,369. The transaction should be carried as a friendly takeover and is expected to be an all-cash deal, financed 60% Amazon’s cash reserves and 40% by debt issuance. Amazon’s shareholders have the potential of capturing $15,800 million and an accretion of 27.5% in 2020.